Effects of NPKS on Yield and Nutrition of BRRI dhan49 - Kamrunnahar, -; Ahmad, S; Iqbal, M; Islam, MN; Islam, A (Bangladesh Rice Journal, 2017)
Nitrogen (N), phosphorus (P), potassium (K) and sulphur (S) strongly influence rice plant nutrition. Present experiment was conducted at the Bangladesh Rice Research Institute (BRRI) farm, Gazipur in a permanent layout in wet season of 2014. Objectives of the research were to study the effects of NPKS on grain yield, plant nutrition, requirement of NPKS to produce one ton grain and to estimate the indigenous nutrient supply of the soil. BRRI dhan49 was tested with NPKS (complete), PKS (-N), NKS (-P), NPS (-K) and NPK (-S) fertilizer packages. The NPKS were applied @ 100-7-80-3 kg ha-1. Omission of each nutrient from the complete treatments significantly reduced grain and straw yields of BRRI dhan49. The highest yield reduction was recorded because of N omission followed by K. Nutrient concentration in grain and straw as well as nutrient uptakes were significantly affected by major plant nutrients. Nutrient uptake was directly related to the biomass production. About 87% of total K uptake remained in straw and thus a good K source for rice cultivation. Nitrogen, P, K, S and Zn required to produce one ton rice were 20.88, 5.04, 18.77, 2.08 and 0.07 kg, respectively. The indigenous N, P, K and S supply capacity of this soil was 37, 13, 41 and 6 kg ha-1, respectively. Bangladesh Rice j. 2016, 20(2): 39-47